Enhancing the performance of service discovery protocol using minimum spanning tree. (20th May 2020) - Jayapal, Cynthia; Jayavel, Senthil; Vanitha, V.
In a wireless sensor network, aggregation is either done to avoid the redundant transmissions. In service provisioning, the control packets sent for service advertisement and discovery contribute significantly to the network traffic. In this paper, it is proposed to aggregate the similar control packets sent from different sources to a common destination along with minimum spanning tree, which is constructed for service provisioning. The mobile agent migration schemes used in the literature have got overhead in finding the migration path. Therefore, the proposed approach uses the spanning tree constructed for service discovery, as the migration path for the mobile agents. It is found from the investigation that the aggregation scheme has reduced average energy spent by 33%, control overhead by 12% and average discovery delay by 25%. Use of mobile agents has reduced the average discovery delay by 22%, control overhead by 19% and service discovery success ratio by 4%.